THE EFFECTIVENESS OF PLATFORM PUZZWORD GAME TO INCREASE STUDENTS' VOCABULARY MASTERY AT SMP NEGERI 2 SONDER - Runturambi, Rivaldy Novi; Noldy Pelenkahu; Paula Hampp (JoTELL : Journal of Teaching English, Linguistics, and Literature, 2023)
This research aims to increase students' vocabulary mastery and evaluating Platform Puzzword's performance as a tool for increasing students' vocabulary and identifying whether using the platform makes a discernible impact on vocabulary development. The subject of the research was 9th-grade students of SMPN 2 SONDER, consisting of 13 students. The research utilized a pre-experimental design with a one-group pre-test and post-test. The findings revealed that students' vocabulary mastery has increased. This increase can be seen from the results of the mean post-test score which only got 52.61, and the mean post-test score which got 75.69. Additionally, the obtained significant value was 0.000, indicating it is smaller than alpha 0.05. Therefore, H0 was rejected, and H1 was accepted or in other words a hypothesis which states that There was no a significant of using Puzzword Game to increased students’ vocabulary mastery at SMP Negeri 2 Sonder is rejected and hypothesis which states that There was a significant of using Puzzword Game to increased students’ vocabulary mastery at SMP Negeri 2 Sonder is accepted. Based on these findings, the researcher concluded that the Puzzword game is effective in increasing students' vocabulary mastery